2012
DOI: 10.1007/s10071-012-0589-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cognition and perseveration by horses, donkeys and mules in a simple A-not-B detour task

Abstract: We investigated perseveration and detour behaviour in 36 equids (Equus caballus, E. asinus, E. caballus × E. asinus) and compared these data to those of a previous study on domestic dogs (Canis familiaris). The animals were required to make a detour through a gap at one end of a straight barrier in order to reach a visible target. After one, two, three or four repeats (A trials), the gap was moved to the opposite end of the barrier (B trials). We recorded initial deviations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 7 publications
2
50
1
Order By: Relevance
“…The hair coat properties of mules were much closer to those of horses than of donkeys. Studies have shown mules to have hybrid vigour in some traits, be intermediate in others, and be inferior to both parent species in others 15, 16, 17. In general, the results here suggest that their hair coat properties are intermediate between their parental species.…”
Section: Discussionsupporting
confidence: 51%
“…The hair coat properties of mules were much closer to those of horses than of donkeys. Studies have shown mules to have hybrid vigour in some traits, be intermediate in others, and be inferior to both parent species in others 15, 16, 17. In general, the results here suggest that their hair coat properties are intermediate between their parental species.…”
Section: Discussionsupporting
confidence: 51%
“…Both donkeys and mules were more accurate and faster problem solvers when challenged to detour through a changing gap to reach a food reward [18]. It is always important to take account of this quick learning ability when training donkeys and mules, as they are able to learn both wanted and unwanted behaviours very quickly.…”
Section: Donkey Behaviourmentioning
confidence: 98%
“…; Osthaus et al. ). However, these studies examined cognition in hybrids created by crossing domesticated species or inbred lines.…”
mentioning
confidence: 97%
“…; Osthaus et al. ; Hoedjes et al. ), and in some cases found that hybrids exhibited enhanced cognition compared to parental species (e.g., Proops et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation